2019
DOI: 10.1681/asn.2019060570
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Repurposed as Antiferroptosis Agents Suppress Organ Damage, Including AKI, by Functioning as Lipid Peroxyl Radical Scavengers

Abstract: BackgroundFerroptosis, nonapoptotic cell death mediated by free radical reactions and driven by the oxidative degradation of lipids, is a therapeutic target because of its role in organ damage, including AKI. Ferroptosis-causing radicals that are targeted by ferroptosis suppressors have not been unequivocally identified. Because certain cytochrome P450 substrate drugs can prevent lipid peroxidation via obscure mechanisms, we evaluated their antiferroptotic potential and used them to identify ferroptosis-causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 63 publications
3
98
0
Order By: Relevance
“…Tissues were fixed in 10% neutral buffered formalin and embedded in paraffin. Kidney sections were stained with Masson’s trichrome, and Sirius red [ 4 , 47 ]. For immunohistochemistry of F4/80, antigen retrieval from deparaffinized sections was performed using Target Retrieval Solution S1700 (Dako, Carpinteria, CA, USA) in an autoclave at 120 °C for five min.…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were fixed in 10% neutral buffered formalin and embedded in paraffin. Kidney sections were stained with Masson’s trichrome, and Sirius red [ 4 , 47 ]. For immunohistochemistry of F4/80, antigen retrieval from deparaffinized sections was performed using Target Retrieval Solution S1700 (Dako, Carpinteria, CA, USA) in an autoclave at 120 °C for five min.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a combination of luciferase reporter, EMSA and ChIP assays, we found that Rev‐erb‐α/β trans‐repress Slc7a11 and HO1 via direct binding to a RORE element, thereby promoting ferroptosis. Ferroptosis is also involved in the development of cisplatin‐, rhabdomyolysis‐ and ischaemia/reperfusion‐induced acute kidney injury in addition to folic acid‐induced acute kidney injury (Guerrero‐Hue et al, 2019; Hu et al, 2019; Mishima et al, 2020). It is tempting to propose that Rev‐erb‐α/β‐based therapeutic strategies are not restricted to folic acid‐induced acute kidney injury but are also applicable to other type of acute kidney injury as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with glycyrrhizin, a HMGB1 inhibitor, could alleviate the degree of liver damage by targeting ferroptosis via inhibition of oxidative stress. Another state-of-the-art study aimed to screen cytochrome P450 substrate compounds with antiferroptotic bioactivity 58 . Their results showed promethazine can ameliorate LPS/GalN-triggered acute liver failure via suppression of lipid peroxidation and decreased cell death.…”
Section: Ferroptosis In Non-cancer Liver Diseasesmentioning
confidence: 99%
“… Disease Ref. Model Compound/target Effect Mechanism/phenotype Acute liver failure 16 LPS/GalN-induced mice L02 cells Glycyrrhizin Inhibition of ferroptosis NRF2, HO-1, and GPx4↑ HMGB1↓ 58 LPS/GalN-induced mice Promethazine Inhibition of ferroptosis NA Acute liver injury 60 PHZ-induced mice/Ad-Sesn2 infected mice HepG2 cells Sestrin2 Inhibition of ferroptosis NRF2, TFR1, ferroportin↑ Alcoholic liver disease 15 SIRT1iKO mice Intestinal sirtuin1 (deficiency) Inhibition of ferroptosis Pro-inflammatory molecules LCN2, SAA1↓ Redox active iron–sulfur CISD1/2↓ 65 Lpin1 -Tg mice Adipose-specific lipin-1 (overexpression) Induction of ferroptosis Adiponectin-sirtuin1, adiponectin-FGF15 axis↓ NF-κB↑ NAFLD 74 CDE diet/MLKL −/− mice Trolox/DFO Inhibition of ferroptosis TNF-α, IL-1β, IL-6↓ Immune-mediated hepatitis 14 ConA-induced/Cav-1 −/− mice Caveolin-1 Inhibition of ferroptosis RNS, iNOS↓ 83 ConA-induced/IDO1 −/− mice IDO1 (deficiency) Inhibition of ferroptosis xCT↑ RNS↓ Ischemia/reperfusion injury 100 I/R mice Liproxstatin-1 Inhibition of ferroptosis MPO↓ 104 HID-fed I/R mice Ferrostatin-1/DFO/α-Tocopherol Inhibition of ferroptosis PTGS2↓ Inflammator...…”
Section: Introductionmentioning
confidence: 99%